2017
DOI: 10.1111/tbed.12666
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virusdetection in dairy products made with milk from experimentally infected cows

Abstract: Summary Vaccinia virus (VACV) is the agent of bovine vaccinia (BV), an emerging zoonosis that causes exanthematic lesions on the teats of dairy cows and on the hands of milkers. The virus has been detected in the milk of naturally infected cows. The objective of this study was to investigate and quantify VACV DNA as well as the presence of infectious virus particles in samples of cheese curd, cheese whey and pasteurized milk produced using milk from cows experimentally inoculated with VACV‐GP2, a Brazilian iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In the following years, other correlated researches would appear, revealing that VACV viral particles could not be inactivated even after thermal treatments of milk and during cheese processing, both in their production and in their maturation period. The detection of infectious viral particles (from both groups I and II) in milk samples and dairy products confirmed this hypothesis [ 80 , 81 , 82 , 83 , 84 ].…”
Section: Classic Transmission and Alternative Routes For Zoonotic Br-vacv Infectionsmentioning
confidence: 75%
See 2 more Smart Citations
“…In the following years, other correlated researches would appear, revealing that VACV viral particles could not be inactivated even after thermal treatments of milk and during cheese processing, both in their production and in their maturation period. The detection of infectious viral particles (from both groups I and II) in milk samples and dairy products confirmed this hypothesis [ 80 , 81 , 82 , 83 , 84 ].…”
Section: Classic Transmission and Alternative Routes For Zoonotic Br-vacv Infectionsmentioning
confidence: 75%
“…It is noteworthy that serological and molecular evidence was detected in naturally and experimentally infected cows, and dairy products produced from the milk of these animals, raising the discussion about the persistence of systemic infection in these animals [ 13 , 84 ]. In addition to this evidence, Borges et al demonstrated that even in rural properties with no record of BV outbreaks, dairy cattle could present neutralizing antibodies against VACV [ 22 ].…”
Section: Classic Transmission and Alternative Routes For Zoonotic Br-vacv Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study on the ingestion of contaminated milk by mice demonstrated systemic infection in the absence of clinical signs (Rehfeld et al, 2015). Reinforcing this possible route of infection, viable VACV has been detected in artisanal cheese samples produced with the milk of experimentally infected dairy cows (de Oliveira et al, 2018). We suggest that similar circumstances might be evident with dairy products derived from water buffaloes.…”
Section: Discussionmentioning
confidence: 93%
“…Studies of experimentally contaminated milk and artisanal cheeses produced with this milk have demonstrated the viability of VACV after a heat treatment at 65 °C, as well as in artisanal cheese and milk stored at low temperatures [ 76 ]. Moreover, viable VACV has been detected in artisanal cheese samples produced with raw milk from experimentally infected dairy cows [ 77 ]. Considering that the virus is secreted via the milk and that it remains viable during the cheese production process, our group analyzed the impact of the ripening process on the viability of VACV in artisanal cheeses [ 78 ].…”
Section: Vaccinia Virus : a Possible Foodborne mentioning
confidence: 99%